Fertilization decreases the effect of ammonium nitrogen on microorganisms in Chinese Carex tibetikobresia meadows during rest-grazing - Zhou, Xuanbo; Wang, Xiaoli; Ma, Yushou; Wang, Yanlong; Ma, Yuan; Xie, Lele (Frontiers in Microbiology, 2025)
IntroductionOn degraded grasslands, rest-grazing and fertilization measures have been widely applied. In alpine grasslands, numerous studies have examined the impact of rest-grazing and fertilizer application on microbial communities. However, the impact of these measures on the microbial community in Carex tibetikobresia meadows remains largely understudied. Furthermore, the relationship between aboveground vegetation and soil components under these treatments warrants further investigation.MethodsWe conducted a field control experiment in Dawu Town, Maqin County, China, during the winter–spring pasture regreen-up period. The primary treatment consisted of five rest-grazing durations, while the secondary treatment involved nitrogen addition.Results and discussionThe results indicated that, under rest-grazing treatment, the levels of soil nitrogen can improve and ammonium nitrogen (NH₄+-N) was the primary environmental factor affecting microbial biomass. It showed a significantly negatively correlated with bacteria and gram-negative bacteria (G−), but a positive correlation with the ratio of gram-positive bacteria to gram-negative bacteria (G+:G−). Furthermore, without fertilization treatment, the ratio of fungi to bacteria (F:B) and G+:G− reached a maximum at rest-grazing for 30 days. In contrast, under fertilization treatment, microbial biomass carbon (MBC) became the dominant environmental factor affecting microbial biomass. It was negatively correlated with G−, but positively correlated with the ratio of F:B and G+:G−. Rest-grazing increases soil inorganic nitrogen and promotes actinomycetes growth, providing a viable strategy for restoring inorganic nitrogen levels in degraded grasslands. On the other hand, fertilization reduced the biomass of total phospholipid fatty acids (PLFAs) and all PLFAs groups. Consequently, the recommendation is that fertilization measures should not be utilized on this grassland and that a 30-day rest-grazing durations is preferable. Additionally, we observed inconsistent responses of microbial communities in the Carex tibetikobresia meadow and alpine meadows to rest-grazing and fertilization. These findings offer valuable insights into how fertilization modifies microbial responses to rest-grazing, providing important guidelines for the management of degraded Carex tibetikobresia meadows.